Setting the stage for improved drying: A stepping stone to solar dryer - Olanipekun, Caleb Ibukun; Salaudeen, Kamaldeen Oladimeji; Totin, Edmond; Yamauchi, Futoshi; Balana, Bedru; Popoola, Olufemi (International Food Policy Research Institute, 2024)
The world population is growing fast, heralding the challenge of feeding over 9.1 billion people with safe food by the year 2050. The amount of food production has increased through efforts made by actors in the agricultural production sector (Bourne, 2014). Food produced globally is sufficient to provide 100% of nutritional requirements of every living human being, but unfortunately, this has not translated to better food security in certain countries in the world, malnutrition has gotten worse in several countries around the world. According to GHI, 64 countries will not reach low hunger, much less zero hunger (SDG2) by 2030, in fact, low hunger status may not be reached globally until 2160.